Sparkol Videoscribe Learning Media for Science Subjects on Human Needs Material - Amalia Nurusyifa; Wulandari, Desi (LPPM Undiksha, 2024)
The most prominent problem in learning Natural and Social Sciences (IPAS) is the less-than-optimal use of learning media, which affects students' learning outcomes. This development research aims to develop Sparkol Videoscribe media on IPAS on human needs material. This type of research is development research. This research applies the ADDIE development model. The research subjects are 1 learning media expert and 1 learning material expert. The subjects of this development research trial are 18 students and grade IV teachers. Data collection techniques are done through interviews, observations, tests, questionnaires and documentation. The data collection instrument uses questions to test the feasibility of the Sparkol videoscribe media. The techniques used to analyze the data are qualitative, quantitative, descriptive analysis, and inferential statistics. The study results showed that Sparkol videoscribe is feasible to use, based on the assessment of media experts by 95.8% and material experts by 90% with very feasible criteria. The media developed is practical based on the t-test and n-gain test with moderate criteria. It is concluded that the Sparkol videoscribe learning media that has been developed is feasible and effective to use in IPAS learning because it can improve students' learning outcomes. The implications of the research are that the Sparkol Videoscribe media developed for science subjects can be used in learning.